Financial Education for Child and Youth Care Practitioners - Lechner, Gerhard; Craß, Ninnia; Kraleva, Dashenka; Scharer, Veronika; Iwański, Jakub; Giraud, Sébastien (Journal of Accounting, Business and Finance Research, 2018)
This paper aims to identify the needs of financial education of Child and Youth Care practitioners (CYCPs). There is not much knowledge about the deficits of financial education of young people in care (YPC) and young care leavers (YCL) and we want to bring more light into this difficult topic. We use focus group interviews in five different countries (Bulgaria, Austria, Germany, Poland, and France) to find the needs of the CYCPs with a special focus on the needs of YCLs. Our focus groups showed that CYCPs do not have enough basic and further education to handle the situation with YPC and YCLs successfully. We found that the needs of the YPC and YCLs concerning financial education are consistent with the needed knowledge, skills and competences of the CYCPs. Some needs of CYCPs and young people in care are to understand the meaning of money, to handle pocket money, to understand the logic of credit and financial contracts and to know how an online bank account works.